Composition and phenology of insect pests of Capsicum (Solanaceae) cultivated in the Makana District, Eastern Cape Province, South Africa - Hepburn, Colleen (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2008)
Capsicum baccatum var. pendulum was first grown in the Makana District in 2005. Extremely little was known about best practices for cultivation or the insects and diseases associated with the crop in this area. The study was conducted during the second year of production, November 2005 and November 2006, in an attempt to identify the composition and phenology of insects occurring on C. baccatum. In the more rural parts of the Eastern Cape, and more particularly in Grahamstown, there are very few industries. With the advent of this new agricultural venture, a processing factory has been opened in Grahamstown creating more than 600 seasonal jobs in the factory and 1000 seasonal jobs on farms for local people. This business enterprise has not only brought about the creation of jobs, but also training and skills development and empowerment, generating much-needed income in this area. An extensive literature review yielded limited information on insect pests associated with Capsicum. Data from a pilot sampling trial undertaken were statistically analyzed to establish the number of plants to be scouted per site and the most effective scouting techniques to use. Based on the data available and insects collected during the pilot sampling trial, a surveillance programme was designed. Five different types of monitoring traps were placed in each of the eight study sites. Collection of trap catches and scouting of fifteen individual plants per site was undertaken on a weekly basis over the 52-week study period. The most commonly occurring potential insect pests were African Bollworm Helicoverpa armigera (Hübner), False Codling Moth Thaumatotibia leucotreta (= Cryptophlebia leucotreta) (Meyrick), Mediterranean Fruit Fly Ceratitis capitata (Wiedemann) and several species of thrips. Population densities of these pests and their phenology on Capsicum were determined. Statistical analyses established the efficacy of the monitoring traps for each pest, tested for differences among and between study sites, calculated an estimate of the number of pods damaged and a measure of plant damage.The results show that the majority of damage caused to the Capsicum baccatum cropping system was due to Mediterranean Fruit Fly populations. It was established that, although African Bollworm and False Codling Moth were present during the study period, their numbers were negligible and only nominal damage was caused by these pests. Damage caused by thrips species was apparent but not quantifiable. Intervention strategies using an Integrated Pest Management approach, are discussed.
Keywords: Insects -- South Africa -- Eastern Cape -- Composition; Insects -- South Africa -- Eastern Cape -- Phenology; Agricultural pests -- South Africa -- Eastern Cape; Peppers -- Diseases and pests -- South Africa -- Eastern Cape; Solanaceae -- Diseases and pests -- South Africa -- Eastern Cape; Insect pests -- South Africa -- Eastern Cape; Insect pests -- Biological control -- South Africa -- Eastern Cape; Insect pests -- Control -- Methods -- South Africa -- Eastern Cape; Insects -- Host plants -- South Africa -- Eastern Cape; Insect-plant relationships -- South Africa -- Eastern Cape